Process for preparing c2-C4 hydrocarbons using hybrid catalysts

By using a hybrid catalyst supported on zirconia and a microporous catalyst component, the carbon-containing gas is converted into C2 to C4 hydrocarbons, which solves the problems of low conversion and rapid reduction of catalyst activity in the prior art, and achieves efficient and stable carbon conversion.

CN119522133APending Publication Date: 2025-02-25DOW GLOBAL TECHNOLOGIES LLC +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380052604.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-22
Filing Date
2023-07-13
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The prior art has problems with low conversion rates and rapid reduction of catalyst activity in converting carbon-containing gases to C2 to C4 hydrocarbons.

Method used

Using a hybrid catalyst, which consists of metal oxide catalyst components supported on zirconium oxide and microporous catalyst components, including gallium oxide and rare earth oxide, converts hydrogen and carbon-containing gases into C2 to C4 hydrocarbons by in-tandem operation.

Benefits of technology

High conversion and stable C2 to C4 hydrocarbon yields are achieved, extending the service life of the catalyst and improving the carbon conversion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119522133A_ABST
    Figure CN119522133A_ABST
Patent Text Reader

Abstract

The present disclosure relates to a process for preparing C2 to C4 hydrocarbons, the process comprising introducing a feed stream comprising hydrogen and a carbonaceous gas selected from the group consisting of carbon monoxide, carbon dioxide and mixtures thereof into a reaction zone of a reactor; and converting the feed stream into a product stream comprising C2 to C4 hydrocarbons in the reaction zone in the presence of a hybrid catalyst. The hybrid catalyst comprises a metal oxide catalyst component and a microporous catalyst component supported on zirconia.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims the benefit of U.S. Provisional Application Serial No. 63 / 391,477, filed on July 22, 2022, the entire disclosure of which is hereby incorporated by reference into this document. Background Art Technical Field

[0003] The present disclosure relates to methods for efficiently converting various carbonaceous streams into C2 to C4 hydrocarbons. In particular, the present disclosure relates to hybrid catalysts and process methods for converting gas feeds into desired hydrocarbon products. Technical Background

[0005] For many industrial applications, hydrocarbons are used in or as starting materials to produce plastics, fuels, and various downstream chemicals. Such hydrocarbons include C2 to C4 materials, such as ethylene, propylene, and butene. A variety of methods have been developed for producing these lower hydrocarbons, including petroleum cracking and various synthesis methods. However, many of these synthesis methods have low carbon conversion rates, and much of the feed carbon (1) is not converted and leaves the method in the same form as the feed gas; (2) is converted to CO2; and / or (3) these synthesis methods have low stability over time, and the catalyst quickly loses its activity to convert the carbon to the desired product. For example, many synthesis methods tend to have catalysts that have rapidly decreasing activity over time - and therefore have reduced C2 to C4 hydrocarbon production. Therefore, there is a need for a method that includes a hybrid catalyst rather than a separate catalytic component that has a high conversion rate of the feed carbon to the desired product (e.g., C2 to C4 hydrocarbons). Summary of the invention

[0006] Embodiments of the present disclosure address these and other needs by preparing hybrid catalysts and methods for using such catalysts. The hybrid catalyst comprises a combination of a metal oxide catalyst component and a microporous catalyst component. The metal oxide catalyst component and the microporous catalyst component are combined into a single catalyst body to form a hybrid catalyst. The metal oxide component and the microporous catalyst component are operated in series so that the hybrid catalyst can be used to directly convert a feed stream comprising hydrogen and a carbonaceous gas (such as synthesis gas) into C2 to C4 hydrocarbons. In addition, the metal oxide catalyst component may comprise both gallium oxide and rare earth oxides, which can improve the stability of the hybrid catalyst during use in a catalytic process.

[0007] According to one or more other aspects of the present disclosure, a method for preparing C2 to C4 hydrocarbons includes introducing a feed stream comprising hydrogen and a carbon-containing gas selected from the group consisting of carbon monoxide, carbon dioxide, and mixtures thereof into a reaction zone of a reactor; and converting the feed stream into a product stream comprising C2 to C4 hydrocarbons in the reaction zone in the presence of a hybrid catalyst. The hybrid catalyst comprises a metal oxide catalyst component supported on zirconium oxide, the metal oxide catalyst component comprising gallium oxide and a rare earth oxide; and a microporous catalyst component comprising a molecular sieve having an 8MR (membered ring) pore opening.

[0008] Additional features and advantages will be set forth in the following Detailed Description, and in part will become apparent to those skilled in the art from that description or may be learned by practicing the embodiments described herein, including the following Detailed Description and claims.

[0009] It is to be understood that both the foregoing general description and the following detailed description describe various embodiments, and are intended to provide an overview or framework for understanding the nature and character of the claimed subject matter. BRIEF DESCRIPTION OF THE DRAWINGS

[0010] FIG. 1 depicts normalized CO conversion as a function of run time using the metal oxide catalyst components described herein. Figure 1A Normalized CO conversion using Comparative Example 1 and Example 1 is depicted. Figure 1B Normalized CO conversion using Comparative Example 1 and Example 2 is depicted. Figure 1C Normalized CO conversion using Example 1 and Example 3 is depicted.

[0011] Figure 2 Plotted are normalized CO conversion as a function of run time using Comparative Example 2 and Example 4 as described herein. DETAILED DESCRIPTION

[0012] Reference will now be made in detail to embodiments of methods for preparing C2 to C4 hydrocarbons from a feed stream comprising hydrogen and carbonaceous gas. As used herein, "carbonaceous gas" refers to a gas selected from carbon monoxide, carbon dioxide and a mixture thereof. Conventional methods exhibit low feed carbon conversion and / or rapid deactivation when they are used, such as by having an increase in methane production or a reduction in synthesis gas conversion, which can result in low olefin yields and / or low stability for a given set of operating conditions within a given amount of time. In contrast, when compared to a hybrid catalyst that does not contain rare earth oxides, the hybrid catalyst comprising rare earth oxides disclosed herein can exhibit high and stable C2 to C4 hydrocarbon (such as C2 to C4 olefin) yields. The preparation and composition of this hybrid catalyst and the method for using this hybrid catalyst are discussed below.

[0013] In embodiments, hybrid catalysts can be closely coupled to the independent reactions of at least two independent catalysts. In the first step, a feed stream (such as synthesis gas) of a carbonaceous gas comprising hydrogen (H2) and a group consisting of a mixture of carbon monoxide (CO), carbon dioxide (CO2) or CO and CO2 can be converted into an intermediate, such as an oxygenated hydrocarbon. In subsequent steps, these intermediates can be converted into a product stream comprising hydrocarbons (mainly short-chain hydrocarbons, such as C2 to C4 hydrocarbons). The continuous formation and consumption of the intermediate oxygenate (oxygenate) formed by the reaction of the second step in the first step can reduce or eliminate the thermodynamic limitations on conversion.

[0014] In an embodiment, the hybrid catalyst includes a metal oxide catalyst component that can convert a feed stream into an oxidized hydrocarbon and a microporous catalyst component that can convert the oxidized hydrocarbon into a hydrocarbon. The metal oxide catalyst component is combined with the microporous catalyst component. It should be understood that, as used herein, "metal oxide catalyst component" includes metals in various oxidation states. In some embodiments, the metal oxide catalyst component may include more than one metal oxide, and each metal oxide in the metal oxide catalyst component may have a different oxidation state. Therefore, the metal oxide catalyst component is not limited to comprising a metal oxide with a uniform oxidation state.

[0015] In an embodiment, the metal oxide catalyst component is supported on zirconium oxide (ZrO2). In an embodiment, the zirconium oxide support of the metal oxide catalyst component can be a phase pure zirconium oxide. As used herein, "phase pure zirconium oxide" refers to zirconium oxide to which no other materials are intentionally added during formation. Thus, phase pure zirconium oxide includes zirconium oxide with small amounts of components other than zirconium (including oxides other than zirconium oxide) that are unintentionally present in the zirconium oxide as a natural part of the zirconium oxide formation process, such as hafnium (Hf). In other embodiments, the zirconium oxide can be a non-phase pure zirconium oxide, such as, but not limited to, zirconium oxide doped with calcium, yttrium oxide, lanthanum, cerium, or a rare earth element.

[0016] In an embodiment, the metal oxide catalyst component comprises gallium oxide. As used herein, "gallium oxide" refers to gallium in various oxidation states. In an embodiment, the gallium oxide may be deposited on the surface of zirconium oxide or form a solid solution with ZrO2. In an embodiment, the gallium oxide may include, but is not limited to, Ga2O3, GaO(OH), and Ga5O 7-(OH). Gallium oxide may also include polymorphs of Ga2O3, such as monoclinic (β-Ga2O3), rhombohedral (α-Ga2O3), defect spinel (γ-Ga2O3), cubic (δ-Ga2O3), or orthorhombic (ε-Ga2O3) structures. In other embodiments, gallium oxide may include gallium in more than one oxidation state. For example, individual galliums may be in different oxidation states. Gallium oxide is not limited to comprising gallium in a uniform oxidation state.

[0017] In an embodiment, the composition of the metal oxide catalyst component is represented by the weight percentage of gallium from gallium oxide. In an embodiment, the weight percentage of gallium can be measured using X-ray fluorescence analysis, assuming complete oxidation equilibrium. In an embodiment, the metal oxide catalyst component may contain less than or equal to 10 weight % gallium based on the total weight of the metal oxide catalyst component. For example, in an embodiment, the metal oxide catalyst component contains less than or equal to 9 weight %, less than or equal to 8 weight %, less than or equal to 7 weight %, less than or equal to 6 weight % or even less than or equal to 5 weight % gallium based on the total weight of the metal oxide catalyst component. In embodiments, the metal oxide catalyst component comprises gallium in an amount of 1 wt % to 10 wt %, 1 wt % to 9 wt %, 1 wt % to 8 wt %, 1 wt % to 7 wt %, 1 wt % to 6 wt %, 1 wt % to 5 wt %, 1 wt % to 4 wt %, 1 wt % to 3 wt %, 2 wt % to 10 wt %, 2 wt % to 9 wt %, 2 wt % to 8 wt %, 2 wt % to 7 wt %, 2 wt % to 6 wt %, 2 wt % to 5 wt %, 2 wt % to 4 wt %, or 2 wt % to 3 wt %, based on the total weight of the metal oxide catalyst component. Without being bound by any particular theory, it is believed that while zirconium oxide or gallium oxide mixed with the microporous solid in the hybrid catalyst can convert the carbonaceous component into C2 to C4 hydrocarbons, it is believed that gallium oxide and zirconium oxide synergistically improve the yield of C2 to C4 hydrocarbons.

[0018] In an embodiment, the metal oxide catalyst component comprises a rare earth oxide. As used herein, "rare earth oxide" refers to an oxide comprising a rare earth element including scandium, yttrium, and elements with atomic numbers from 57 to 71, such as, but not limited to, samarium, gadolinium, dysprosium, lanthanum, cerium, and neodymium.

[0019] In an embodiment, the composition of the metal oxide catalyst component is represented by the weight percentage of the rare earth elements from the rare earth oxide. In an embodiment, the weight percentage of the rare earth elements can be measured using X-ray fluorescence analysis, assuming complete oxidation equilibrium. In an embodiment, based on the total weight of the metal oxide catalyst component, the metal oxide catalyst component may include less than or equal to 7 weight % of rare earth elements. For example, in an embodiment, based on the total weight of the metal oxide catalyst component, the metal oxide catalyst component includes less than or equal to 6 weight % or even less than or equal to 5 weight % of rare earth elements. In an embodiment, the metal oxide catalyst component includes more than 1 weight %, more than 2 weight % or even more than 3 weight % of rare earth elements. In an embodiment, based on the total weight of the metal oxide catalyst component, the metal oxide catalyst component includes 1 weight % to 7 weight %, 1 weight % to 6 weight %, 1 weight % to 5 weight %, 1 weight % to 4 weight %, 2 weight % to 7 weight %, 2 weight % to 6 weight %, 2 weight % to 5 weight % or 2 weight % to 4 weight % of rare earth elements. Without being bound by any particular theory, it is believed that adding rare earth oxides to the metal oxide catalyst component can reduce the deactivation rate of the catalytic reaction (such as the conversion of carbonaceous gas to C2-C4 hydrocarbons) of the hybrid catalyst comprising the metal oxide catalyst component. It is also believed that adding rare earth oxides to the metal oxide catalyst component can increase the stability of the metal oxide catalyst component during the catalytic reaction. It is believed that less than 1% by weight of rare earth elements in the metal oxide catalyst component may not provide a sufficient reduction in the deactivation rate of the hybrid catalyst comprising the metal oxide catalyst component. In addition, it is believed that greater than 7% by weight of rare earth elements in the metal oxide catalyst component can reduce the catalytic activity of the hybrid catalyst.

[0020] In other cases, additional rare earth elements and / or transition metals may be co-deposited with the gallium precursor or introduced only when a mixed composition comprising gallium oxide and zirconium oxide has been first prepared. For example, in embodiments, the metal oxide catalyst component may also include a transition metal element such as nickel (Ni), palladium (Pd), or platinum (Pt).

[0021] In view of the above, one method of preparing the metal oxide catalyst component of the hybrid catalyst is by incipient wetness impregnation. In this method, an aqueous mixture of a gallium precursor material (such as gallium (III) nitrate hydrate (Ga (NO3) 3 · xH2O) and an aqueous mixture of a rare earth element precursor material (such as lanthanum (III) nitrate hexahydrate (La (NO3) 3 · 6H2O)) is added to zirconium oxide (such as zirconium oxide powder or solution) to form a mixture. The amount of each material in the mixture can be controlled based on the desired ratio of gallium to zirconium oxide, rare earth element to zirconium oxide, or gallium to rare earth element. In other embodiments, gallium oxide and / or rare earth oxide can be deposited or distributed on zirconium oxide by chemical vapor deposition (CVD) methods. However, the method for preparing the metal oxide catalyst component of the hybrid catalyst is not particularly limited, and any method that can apply a fine layer of gallium oxide and rare earth oxide to the surface of zirconium oxide can be used according to the embodiment. It should be understood that the total amount of gallium precursor and rare earth element precursor mixed with zirconium oxide will be determined based on the desired target amount of gallium and rare earth element in the metal oxide catalyst component.

[0022] As previously discussed, the metal oxide catalyst component may be supported on zirconium oxide. In an embodiment, the zirconium oxide may include zirconium oxide particles having a crystalline structure. In an embodiment, the zirconium oxide includes zirconium oxide particles having a monoclinic structure. In one or more embodiments, the zirconium oxide consists essentially of crystalline zirconium oxide particles or consists of crystalline zirconium oxide particles. In an embodiment, the zirconium oxide consists essentially of monoclinic zirconium oxide particles or consists of monoclinic zirconium oxide particles. According to some embodiments, the BET surface area of ​​the zirconium oxide is greater than or equal to 5 square meters per gram (m2 / g). 2 / g), such as greater than 10m 2 / g, greater than 20m 2 / g, greater than 30m 2 / g, greater than 40m 2 / g, greater than 50m 2 / g, greater than 60m 2 / g, greater than 70m 2 / g, greater than 80m 2 / g, greater than 90m 2 / g, greater than 100m 2 / g, greater than 110m 2 / g, greater than 120m 2 / g, greater than 130m 2 / g or greater than 140m 2 According to some embodiments, the maximum BET surface area of ​​the zirconium oxide particles is 150 m 2 / g. Therefore, in some embodiments, the BET surface area of ​​zirconia is 5m 2 / g to 150m2 / g, 10m 2 / g to 150m 2 / g, 20m 2 / g to 150m 2 / g, such as 30m 2 / g to 150m 2 / g, 40m 2 / g to 150m 2 / g, 50m 2 / g to 150m 2 / g, 60m 2 / g to 150m 2 / g, 70m 2 / g to 150m 2 / g, 80m 2 / g to 150m 2 / g, 90m 2 / g to 150m 2 / g、100m 2 / g to 150m 2 / g, 110m 2 / g to 150m 2 / g, 120m 2 / g to 150m 2 / g, 130m 2 / g to 150m 2 / g or 140m 2 / g to 150m 2 / g. In some embodiments, the BET surface area of ​​zirconium oxide is 5m 2 / g to 140m 2 / g, such as 5m 2 / g to 130m 2 / g, 5m 2 / g to 120m 2 / g, 5m 2 / g to 110m 2 / g, 5m 2 / g to 100m 2 / g, 5m 2 / g to 90m 2 / g, 5m 2 / g to 80m 2 / g, 5m 2 / g to 70m 2 / g, 5m 2 / g to 60m 2 / g, 5m 2 / g to 50m 2 / g, 5m 2 / g to 40m 2 / g, 5m 2 / g to 30m 2 / g, 5m 2 / g to 20m 2 / g or 5m 2 / g to 10m 2 / g. In some embodiments, the BET surface area of ​​zirconium oxide is 10m 2 / g to 140m 2 / g, 20m 2 / g to 130m 2 / g, 30m 2 / g to 120m 2 / g, 40m 2 / g to 110m 2 / g, 50m 2 / g to 100m 2 / g, 60m 2 / g to 90m 2 / g or 70m 2 / g to 80m 2 / g.

[0023] In embodiments, once the gallium precursor material, rare earth element precursor material, and zirconium oxide are thoroughly mixed, the metal oxide catalyst component may be dried at a temperature below 200 degrees Celsius (°C), such as below 175°C, below 150°C, below 100°C, or about 85°C. After drying, the metal oxide catalyst component may be heated at 400°C to 800°C, such as 400°C to 775°C, 400°C to 750°C, 400°C to 725°C, 400°C to 700°C, 400°C to 675°C, 400°C to 650°C, 400°C to 625°C, 400°C to 600°C, 500°C to 800°C, 500°C to 775°C, 500°C to 750°C, 500°C to 725°C, 500°C to 700°C, 500°C to 675°C, 500°C to 650°C, 550°C to 80 .... 0° C. to 775° C., 550° C. to 750° C., 550° C. to 725° C., 550° C. to 700° C., 550° C. to 675° C., 550° C. to 650° C., 600° C. to 800° C., 600° C. to 775° C., 600° C. to 750° C., 600° C. to 725° C., 600° C. to 700° C., 600° C. to 675° C., 600° C. to 650° C., 650° C. to 800° C., 650° C. to 775° C., 650° C. to 750° C., 650° C. to 725° C., 650° C. to 700° C., or 700° to 800° C. After calcination, the composition of the mixed metal oxide catalyst component is determined and can be reported as the gallium weight and rare earth element weight as disclosed herein.

[0024] Without being bound by any particular theory, it is believed that calcining the metal oxide catalyst component at a higher temperature can result in improved catalytic stability of the metal oxide catalyst component and / or a hybrid catalyst comprising the metal oxide catalyst component during a catalytic reaction (such as the conversion of a carbonaceous gas to a C2-C4-hydrocarbon). Higher calcination temperatures can reduce the BET surface area of ​​the metal oxide catalyst component, which can reduce catalytic activity. However, the inclusion of rare earth elements in the metal oxide catalyst component can allow the metal oxide catalyst component to maintain a higher BET surface area, even when calcined at a higher temperature. It is believed that calcining the metal oxide catalyst component at a temperature greater than 800° C. can result in a greater loss of the BET surface area of ​​the catalyst, which can reduce the overall performance of the catalyst. It is believed that calcining the metal oxide catalyst component at a temperature less than 400° C. can result in structural changes in the hybrid catalyst during use in a catalytic operation.

[0025] It should be understood that, according to embodiments, the metal oxide catalyst component can be made by other methods that ultimately produce intimate contact and / or dispersion between the gallium precursor, the rare earth element precursor and the zirconium oxide. Some non-limiting examples include vapor deposition of a Ga-containing precursor and / or a rare earth element-containing precursor (organic or inorganic in nature), followed by controlled decomposition thereof. Similarly, the method for dispersing liquid gallium metal can be modified by a person skilled in the art to produce intimate contact between the gallium precursor, the rare earth element precursor and the zirconium oxide.

[0026] In embodiments, after the metal oxide catalyst component has been prepared such as by the method disclosed above, the metal oxide catalyst component can be mixed with a microporous catalyst component and a binder to form a single catalyst. In embodiments, the microporous catalyst component can be selected from a molecular sieve with an 8-MR pore opening and a framework type selected from the group consisting of the following framework types: CHA, AEI, AFX, ERI, LEV, LTA, UFI, RTH, EDI, GIS, MER, RHO and combinations thereof, which corresponds to the naming convention of the International Zeolite Association (International Zeolite Association). It should be understood that in embodiments, both aluminosilicate and silicoaluminophosphate frameworks can be used. Some embodiments may include tetrahedral aluminosilicates, ALPO (such as, for example, tetrahedral aluminophosphates), SAPO (such as, for example, tetrahedral silicoaluminophosphates) and only silica-based framework silicates. In certain embodiments, the microporous catalyst component can be a silicoaluminophosphate with a chabazite (CHA) framework type. Examples of these silicoaluminophosphates may include, but are not necessarily limited to: CHA embodiments selected from SAPO-34 and SSZ-13; and AEI embodiments, such as SAPO-18 and SSZ-13. Combinations of microporous catalyst components having any of the above framework types may also be employed. It should be understood that, depending on the desired product, the microporous catalyst component may have different ring pore openings. For example, depending on the desired product, a microporous catalyst component having an 8-MR to 12-MR pore opening may be used. However, in order to produce C2 to C4 hydrocarbons, a microporous catalyst component having an 8-MR pore opening is used in an embodiment.

[0027] The metal oxide catalyst component and the microporous catalyst component can be combined in a mass ratio of 1:10 to 10:1, 1:10 to 9:1, 1:10 to 8:1, 1:10 to 5:1, 1:10 to 4:1, 1:10 to 3:1, 1:8 to 8:1, 1:8 to 7:1, 1:8 to 6:1, 1:8 to 5:1, 1:8 to 4:1, 1:5 to 8:1, 1:5 to 7:1, 1:5 to 6:1, or 1:5 to 5:1.

[0028] In embodiments, a binder may be added to a mixture of the metal oxide catalyst component and the microporous catalyst component to produce a paste. The binder may be able to hold the metal oxide catalyst component and the microporous catalyst component together. The paste may be extruded to produce a hybrid catalyst. The hybrid catalyst may be formed by any suitable extrusion method.

[0029] Various binders are considered suitable. For example, the binder may include alumina, zirconium oxide, or both. In an embodiment, the binder may include pure alumina. In an embodiment, the binder may include pure zirconium oxide. When the binder includes alumina, the alumina binder may be hydrated alumina. The hydrated alumina composition may be prepared by a boehmite precursor with water and a peptizing agent. The binder may be mixed with a metal oxide catalyst component and a microporous catalyst component. After the binder is mixed with the metal oxide catalyst component and the microporous catalyst component, the mixture may be extruded, dried, and calcined. After calcination, the binder may form alumina and bond the metal oxide catalyst component and the microporous catalyst component together to provide mechanical strength for extruding a hybrid catalyst. In an embodiment, the binder is a colloidal solution, suspension, or gel of a binder precursor. The binder precursor may include an oxide or hydroxide of aluminum, an oxide or hydroxide of zirconium, or a mixture thereof. In one embodiment, the binder precursor may include pure alumina, (pseudo) boehmite, or gibbsite, or a mixture thereof. In other embodiments, the binder precursor may include pure zirconium oxide, hydrated zirconium oxide, or mixtures thereof.

[0030] The metal oxide catalyst component and the microporous catalyst component of the hybrid catalyst can be mixed together by any suitable means to achieve uniform mixing of all components before extrusion. The metal oxide catalyst component and the microporous catalyst component can be mixed in powder form initially, to achieve uniformity in a suitable dry mixer, such as a ribbon or plow mixer. The binder precursor of peptization can be added to the mixture of the metal oxide catalyst component and the microporous catalyst component, and mixed in a suitable heavy industrial mixer capable of handling thick paste formulations. Alternatively, the premixed metal oxide catalyst component and the microporous catalyst component of the dry can be directly fed into the feed screw of a screw extruder together with the binder precursor composition of peptization, and directly mixed in the screw extruder. The hybrid catalyst can be extruded into a desired shape by any suitable extrusion method. The example of shape includes pellet, spherical or nearly spherical. In an embodiment, the metal oxide catalyst component may comprise from 1.0 weight percent (wt. %) to 85.0 wt. %, such as from 5.0 wt. % to 80.0 wt. %, from 10.0 wt. % to 80.0 wt. %, from 15.0 wt. % to 80.0 wt. %, from 20.0 wt. % to 80.0 wt. %, from 25.0 wt. % to 80.0 wt. %, from 30.0 wt. % to 80.0 wt. %, from 35.0 wt. % to 80.0 wt. %, from 40.0 wt. % to 80.0 wt. %, from 45.0 wt. % to 80.0 wt. %, from 50.0 wt. % to 80.0 wt. %, from 55.0 wt. % to 80.0 wt. %, from 60.0 wt. % to 80.0 wt. %, from 65.0 wt. % to 80.0 wt. %, from 70.0 wt. % to 80.0 wt. %, or from 75.0 wt. % to 80.0 wt. In some embodiments, the metal oxide catalyst component comprises 1.0 wt % to 80.0 wt %, 1.0 wt % to 75.0 wt %, 1.0 wt % to 70.0 wt %, 1.0 wt % to 65.0 wt %, 1.0 wt % to 60.0 wt %, 1.0 wt % to 55.0 wt %, 1.0 wt % to 50.0 wt %, 1.0 wt % to 45.0 wt %, 1.0 wt % to 40.0 wt %, 1.0 wt % to 35.0 wt %, 1.0 wt % to 30.0 wt %, 1.0 wt % to 25.0 wt %, 1.0 wt % to 20.0 wt %, 1.0 wt % to 15.0 wt %, 1.0 wt % to 10.0 wt %, or 1.0 wt % to 5.0 wt %.In some embodiments, the metal oxide catalyst component accounts for 5.0% to 80.0% by weight of the hybrid catalyst, such as 10.0% to 80.0% by weight, 15.0% to 80.0% by weight, 20.0% to 80.0% by weight, 25.0% to 75.0% by weight, 30.0% to 70.0% by weight, 35.0% to 65.0% by weight, 40.0% to 60.0% by weight, or 45.0% to 55.0% by weight. In some embodiments, the metal oxide catalyst component accounts for 50.0% to 80.0% by weight of the hybrid catalyst, such as 50.0% to 75.0% by weight, 50.0% to 70.0% by weight, 60.0% to 80.0% by weight, 60.0% to 75.0% by weight, or 60.0% to 70.0% by weight.

[0031] In other embodiments, the metal oxide catalyst component and the microporous catalyst component of the hybrid catalyst may be mixed together by any suitable means available to those skilled in the art, including but not limited to physical mixing of separate catalysts, bifunctional catalyst pellets, and bifunctional catalyst extrudates.

[0032] In embodiments, the binder may combine the metal oxide catalyst component and the microporous catalyst component into a single catalyst body that may improve C2 to C4 hydrocarbon yield and carbon conversion compared to a physical mixture comprising the metal oxide catalyst component and the microporous catalyst component separately.

[0033] In embodiments, the binder may be a colloidal solution, suspension or gel of a binder precursor. The binder precursor may include an oxide or hydroxide of aluminum, an oxide or hydroxide of zirconium or a mixture thereof. In one embodiment, the binder precursor may include pure alumina, (pseudo)boehmite or gibbsite or a mixture thereof. In other embodiments, the binder precursor may include pure zirconium oxide, hydrated zirconium oxide or a mixture thereof. In embodiments where the binder includes hydrated alumina (e.g., pseudoboehmite or gibbsite), an acid is typically added as a peptizing agent. The peptization ratio is defined as the ratio of the number of moles of acid added during peptization to the number of moles of aluminum ([H + ] / [Al]). In one or more embodiments, the peptization ratio may have a [H] of 0.005 to 0.1, 0.01 to 0.1, or about 0.05. + ] / [Al] ratio.

[0034] Without being bound by any particular theory, it has been found that using templated molecular sieves (e.g., uncalcined) for formulation has a positive impact on catalyst performance and structural characteristics, particularly when strongly acidic conditions, such as [H] greater than 0.05 or greater than 0.025, are used during the formulation protocol of the hybrid catalyst. +] / [Al] ratio.

[0035] In an alternative embodiment, the zirconia support may be first mixed with the microporous component and the binder to obtain the hybrid catalyst support. Alternatively, the zirconia support may be generated in situ during the calcination of the hybrid catalyst support. The active metal oxide catalyst component (e.g., gallium, lanthanide and / or transition metal) may then be added to the hybrid catalyst support by any means known to those skilled in the art to obtain the hybrid catalyst, as described in detail above.

[0036] In some embodiments, the metal oxide catalyst component and / or the binder are substantially free of silicon and phosphorus. The term "substantially free" means that the component is less than 0.5 weight percent (wt.%) in the composition. For example, based on the combined weight of the mixed metal oxide and binder, the mixed metal oxide catalyst component and binder that are substantially free of silicon and phosphorus may have less than 0.5 weight % silicon and phosphorus. Without being bound by any particular theory, it is believed that the reduction of silicon and phosphorus in the metal oxide catalyst component and / or the binder can improve the catalytic performance of the hybrid catalyst.

[0037] The hybrid catalyst can be used in a process for converting carbon in a carbon-containing feed stream into C2 to C4 hydrocarbons. Such a process will be described in more detail below.

[0038] A method for preparing C2 to C4 hydrocarbons comprises introducing a feed stream comprising hydrogen and a carbon-containing gas selected from the group consisting of carbon monoxide, carbon dioxide and mixtures thereof into a reaction zone of a reactor; and converting the feed stream into a product stream comprising C2 to C4 hydrocarbons in the reaction zone in the presence of a hybrid catalyst.

[0039] According to an embodiment, a feed stream is fed into a reaction zone, the feed stream comprising hydrogen (H2) and a carbon-containing gas selected from carbon monoxide (CO), carbon dioxide (CO2) and a combination thereof. In some embodiments, based on the combined volume of H2 gas and a gas selected from CO, CO2 and a combination thereof, H2 gas is present in the feed stream in an amount of 10 volume percent (vol%) to 90vol%. The feed stream is contacted with a hybrid catalyst as disclosed and described herein in the reaction zone. The hybrid catalyst includes a metal oxide catalyst component supported on zirconium oxide. The metal oxide catalyst component includes gallium oxide and a rare earth oxide. The hybrid catalyst may also include a microporous catalyst component, which includes a molecular sieve having an 8-MR (ring-membered) pore opening.

[0040] It is understood that the activity of the hybrid catalyst will be higher for feed streams containing CO as the carbon-containing gas, and that the activity of the hybrid catalyst will decrease when a larger portion of the carbon-containing gas in the feed stream is CO. However, this is not to say that the hybrid catalysts disclosed and described herein cannot be used in processes where the feed stream contains CO as all or a majority of the carbon-containing gas.

[0041] The feed stream is contacted with the hybrid catalyst in a reaction zone under reaction conditions sufficient to form a product stream comprising C2 to C4 hydrocarbons. According to one or more embodiments, the reaction conditions include a temperature in the reaction zone ranging from 350°C to 480°C, such as 375°C to 450°C, 400°C to 450°C, 350°C to 425°C, 375°C to 425°C, 400°C to 425°C, 350°C to 400°C, or 375°C to 400°C.

[0042] In embodiments, the reaction conditions include a pressure within the reaction zone of at least 1 bar (100 kilopascals (kPa), such as at least 5 bar (500 kPa), at least 10 bar (1,000 kPa), at least 15 bar (1,500 kPa), at least 20 bar (2,000 kPa), at least 25 bar (2,500 kPa), at least 30 bar (3,000 kPa), at least 35 bar (3,500 kPa), at least 40 bar (4,000 kPa), at least 45 bar (4,500 kPa), at least 50 bar (500 kPa), at least 55 bar (600 kPa), at least 50 bar (700 kPa), at least 50 bar (800 kPa), at least 55 bar (900 kPa), at least 50 bar (1000 kPa), at least 50 bar (1100 kPa), at least 50 bar (1200 kPa), at least 50 bar (1300 kPa), at least 50 bar (1500 kPa), at least 50 bar (1600 kPa), at least 50 bar (1700 kPa), at least 50 bar (1800 kPa), at least 50 bar (1900 kPa), at least 50 bar (1900 kPa), at least 50 bar (1 kPa), at least 50 bar (5,000 kPa), at least 55 bar (5,500 kPa), at least 60 bar (6,000 kPa), at least 65 bar (6,500 kPa), at least 70 bar (7,000 kPa), at least 75 bar (7,500 kPa), at least 80 bar (8,000 kPa), at least 85 bar (8,500 kPa), at least 90 bar (9,000 kPa), at least 95 bar (9,500 kPa), or at least 100 bar (10,000 kPa). In other embodiments, the reaction conditions include a pressure within the reaction zone of 5 bar (500 kPa) to 100 bar (10,000 kPa), such as 10 bar (1,000 kPa) to 95 bar (9,500 kPa), 15 bar (1,500 kPa) to 90 bar (9,000 kPa), 20 bar (2,000 kPa) to 85 bar (8,500 kPa), 25 bar (2,500 kPa) to 80 bar (8,000 kPa), 30 bar (3,000 kPa) to 55 bar (8,500 kPa), 35 bar (2,500 kPa) to 80 bar (8,000 kPa), 30 bar (3,000 kPa) to 50 bar (8,000 kPa), 35 ...500 kPa), 35 bar (3,000 kPa) to 50 bar (8,000 kPa), 35 bar (3,000 kPa) to 50 bar (8,500 kPa), 35 bar (3,000 kPa) to 50 bar (8 In some embodiments, the pressure inside the reaction zone is from 20 bar (2,000 kPa) to 60 bar (6,000 kPa).

[0043] According to embodiments, the gas hourly space velocity (GHSV) in the reaction zone is from 500 per hour ( / hr) to 12,000 / hr, such as from 500 / hr to 10,000 / hr, from 1,200 / hr to 12,000 / hr, from 1,500 / hr to 10,000 / hr, from 2,000 / hr to 9,500 / hr, from 2,500 / hr to 9,000 / hr, from 3,000 / hr to 8,500 / hr, from 3,500 / hr to 8,000 / hr, from 4,000 / hr to 7,500 / hr, from 4,500 / hr to 7,000 / hr, from 5,000 / hr to 6,500 / hr, or from 5,500 / hr to 6,000 / hr. In some embodiments, the GHSV within the reaction zone is 1,800 / hour to 3,600 / hour, such as 2,000 / hour to 3,600 / hour, 2,200 / hour to 3,600 / hour, 2,400 / hour to 3,600 / hour, 2,600 / hour to 3,600 / hour, 2,800 / hour to 3,600 / hour, 3,000 / hour to 3,600 / hour, 3,200 / hour to 3,600 / hour, or 3,400 / hour to 3,600 / hour. In some embodiments, the GHSV in the reaction zone is 1,800 / hour to 3,400 / hour, such as 1,800 / hour to 3,200 / hour, 1,800 / hour to 3,000 / hour, 1,800 / hour to 2,800 / hour, 1,800 / hour to 2,600 / hour, 1,800 / hour to 2,400 / hour, 1,800 / hour to 2,200 / hour, or 1,800 / hour to 2,000 / hour. In some embodiments, the GHSV in the reaction is 2,000 / hour to 3,400 / hour, such as 2,200 / hour to 3,200 / hour, 2,400 / hour to 3,000 / hour, or 2,600 / hour to 2,800 / hour.

[0044] In embodiments, using the hybrid catalyst disclosed and described herein and the process conditions disclosed and described herein, the process stability and / or productivity of the hybrid catalyst can be improved by maintaining a high carbon conversion. Within the disclosed method range, the conversion of the feed containing carbon oxides and hydrogen can be carried out in a series of reactors, wherein the water by-product is separated (knock-out) by means of, for example, phase separation, membrane separation or some type of water selective absorption or adsorption method. Further continuously directing the partial conversion and anhydrous effluent to subsequent reactors and repeating this technical mode of operation will have the overall effect of improving olefin yield.

[0045] In embodiments, the process may have a C2-C3 olefin selectivity / paraffin selectivity ratio greater than or equal to 2, 2 to 20, 2 to 10, 2 to 8, 2 to 6, 3 to 11, 3 to 10, 3 to 8, 3 to 6, or about 4 using the hybrid catalysts disclosed and described herein and the process conditions disclosed and described herein.

[0046] Example

[0047] The following examples illustrate features of the present disclosure, but are not intended to limit the scope of the present disclosure. For each of the following examples and comparative examples, the microporous catalyst component was prepared as follows: SAPO-34 was synthesized according to literature procedures (Lok, BM; Messina, CA; Patton, RL; Gajek, RT; Cannan, TR; Flanigen, EM Crystalline silicoaluminophosphates (US Pat. No. 4,440,871A, 1984). When calcined SAPO-34 was used, the material was calcined in air using the following procedure: from 25°C to 600°C at a heating rate of 2°C / min, maintained at 600°C for 4 hours (h), and cooled to 25°C within 4 hours.

[0048] Example 1

[0049] A metal oxide catalyst component comprising gallium and lanthanum on a zirconium oxide support was prepared by incipient wetness impregnation. An impregnation solution of gallium (III) nitrate hydrate (Ga(NO3)3·xH2O) and lanthanum (III) nitrate hexahydrate (La(NO3)3·6H2O) at concentrations of 0.86 mol / L and 0.86 mol / L, respectively, in deionized water was prepared. 2 g of a 40 mesh (400 μm) to 80 mesh (177 μm) ZrO2 support (manufactured by NORPRO, product code SZ31164, BET surface area = 100 m 2 / g, more than 95% monoclinic phase as measured by XRD, pore volume measured by deionized water = 0.4 mL / g) and placed in a glass vial. Afterwards, 0.8 mL of Ga and La impregnation solution was added dropwise to the support while shaking continuously. After impregnation, the metal oxide catalyst components were dried overnight at 80°C in a forced convection oven and calcined in a muffle furnace using the following procedure: heating from 25°C to 550°C at a heating rate of 3°C / min, and kept at 550°C for 4 hours. After calcination, the catalyst was re-screened to 40 mesh to 80 mesh.

[0050] Example 2

[0051] A metal oxide catalyst component containing gallium on a zirconium oxide support was prepared by incipient wetness impregnation. An impregnation solution of gallium (III) nitrate hydrate (Ga(NO3)3·xH2O) at a concentration of 0.86 mol / L in deionized water was prepared. 2 g of a 40 mesh (400 μm) to 80 mesh (177 μm) ZrO2 support (manufactured by NORPRO, product code SZ31164, BET surface area = 100 m 2 / g, more than 95% monoclinic phase obtained by XRD, pore volume measured by deionized water = 0.4 mL / g) and placed in a glass vial. After that, 0.8 mL of Ga impregnation solution was added dropwise to the support while shaking continuously. After impregnation, the metal oxide catalyst component was dried at 80°C for 12 hours in a forced convection oven and calcined in a muffle furnace using the following procedure: heating from 25°C to 700°C at a heating rate of 3°C / min, and kept at 700°C for 4 hours. After calcination, the catalyst was re-screened to 40 mesh to 80 mesh.

[0052] Example 3

[0053] The metal oxide catalyst component was prepared according to Example 1, but calcined from 25°C to 700°C at a heating rate of 3°C / min and held at 700°C for 4 hours.

[0054] Example 4

[0055] A metal oxide catalyst component comprising gallium and lanthanum on a zirconium oxide support was prepared by incipient wetness impregnation. An impregnation solution of gallium (III) nitrate hydrate (Ga(NO3)3·xH2O) and lanthanum (III) nitrate hexahydrate (La(NO3)3·6H2O) at concentrations of 0.73 mol / L and 0.22 mol / L, respectively, in deionized water was prepared. 10 g of a ZrO2 support (manufactured by Daiichi Kigenso Kagaku-Kogyo CO., LTD. (DKKK), product code Z3186, BET surface area = 85 m 2 / g, more than 95% monoclinic phase as measured by XRD, pore volume measured by deionized water = 0.55mL / g) and placed in a glass vial. Afterwards, 5.5mL of Ga and La impregnation solution was added dropwise to the support while shaking continuously. After impregnation, the metal oxide catalyst component was dried at 85°C for 12 hours in a forced convection oven and calcined in a muffle furnace using the following procedure: heating from 25°C to 700°C at a heating rate of 3°C / min, and kept at 700°C for 4 hours. After calcination, the catalyst was re-screened to less than 200 mesh size (less than 75μm) to remove larger agglomerated particles.

[0056] Powder was prepared by mixing 8.0g of the above-mentioned metal oxide catalyst component with 1.808g of uncalcined SAPO-34 (less than 200 mesh diameters, less than 75 μm) for 10 minutes using a mortar and pestle. Individually, HNO (65% by weight of H o solution) was used by pseudo-boehmite (AlOOH) (manufactured by Sasol, trade name Catapal D) with 0.05 HNO / Al ratio and 35% by weight of total solids peptized in water. Peptized pseudo-boehmite mixture was added to dry powder to form a paste, and the target was 24.6% by weight based on total solids (Catapal D, SAPO-34 and metal oxide) pseudo-boehmite concentration. Subsequently, a mortar and pestle was used to mix the paste for at least 10 minutes, until a paste that could be extruded was obtained. The paste was transferred to a ceramic dish and dried at 85°C for 12 hours to form a dry precursor. The dried precursor was heated from 25°C to 600°C at a heating rate of 2°C / min in a stationary muffle furnace and maintained at 600°C for 4 hours to form a hybrid catalyst. After calcination, the hybrid catalyst was crushed and sieved into 40 mesh (400 μm) to 80 mesh (177 μm) for testing.

[0057] Comparative Example 1

[0058] The metal oxide catalyst component was prepared according to Example 2, but calcined from 25°C to 550°C at a heating rate of 3°C / min and held at 550°C for 4 hours.

[0059] Comparative Example 2

[0060] The hybrid catalyst was prepared according to Example 4, but the metal oxide catalyst component was calcined from 25°C to 550°C at a heating rate of 3°C / min and held at 550°C for 4 hours.

[0061] Example 5 - Catalyst Composition Data

[0062] The weight percentages of gallium and lanthanum in the oxide form (assuming oxygen balance) that make up the metal oxide catalyst component in Examples 1, 2, 3 and Comparative Example 1 were determined by X-ray fluorescence and reported in Table 1. Additionally, the calcination temperatures, the weight percentages of tetragonal zirconia (t-ZrO2) relative to the total weight of zirconia, and the BET surface areas of Examples 1 to 3 and Comparative Example 1 are also reported in Table 1. The t-ZrO2 weight % was approximated by whole pattern fitting of X-ray diffraction data using JADE professional software, which uses the most stable oxidation stoichiometry. The BET surface area was calculated by N2 physical adsorption using Micromeritics Tristar3020. Prior to BET measurement, each sample was pretreated for 2 hours at 200 °C under nitrogen using a degassing module SmartPrep 065 (Micromeritics Instrument Corporation). Using nitrogen as the adsorbate with a molecular cross-sectional area of 0.162 nm 2 an adsorption / desorption isotherm was recorded at 77.4 K. A macro-based Excel tool was used to process the data in the region of the partial pressure range 0.05 < p / p0 < 0.3 with an R squared value of linear fit > 0.999. To determine the pore volume and pore distribution, adsorption and desorption isotherms were measured with the same adsorbate (from 0.05 up to 1 partial pressure (p / p0) and back to 0.05).

[0063] Table 1

[0064] catalyst Ga, weight% La, weight% Calcination temperature, °C <![CDATA[t-ZrO2,%]]> <![CDATA[BET,m 2 / g]]> Example 1 2.74 3.89 550 10.0 82.57 Example 2 2.99 0 700 7.50 44.60 Example 3 2.79 3.99 700 10.3 70.80 Comparative Example 1 2.90 0 550 8.50 68.77

[0065] As shown in Table 1, comparison of Example 2 with Comparative Example 1 shows that calcining the metal oxide catalyst component at a higher temperature results in a decrease in the BET surface area from 68.77 m2 / g to 44.60 m 2 / g. Comparison of Example 1 with Comparative Example 1 shows that addition of lanthanum to the metal oxide catalyst component results in an increase in the BET surface area from 68.77 m2 / g to 82.57 m 2 / g. Additionally, comparison of Example 3 with Example 1 shows that calcining the lanthanum-containing metal oxide catalyst component at a higher temperature results in a modest decrease in the BET surface area from 82.57 m2 / g to 70.80 m 2 / g. Thus, compared to a metal oxide catalyst component that does not contain rare earth oxides, inclusion of rare earth oxides in the metal oxide catalyst component enables improved stability at higher calcination temperatures while only modestly affecting the BET surface area.

[0066] Example 6 - Catalytic Performance Data

[0067] Prior to testing, the mixed metal oxide catalysts described in Examples 1 to 3 and Comparative Example 1 were physically mixed with calcined SAPO-34 of 40 to 80 mesh sieve fractions at a mass ratio of 4:1. Testing of the hybrid catalyst was performed in a stainless steel fixed bed reactor system (7.7 mm inner diameter, 38.4 cm length) under the following conditions: 420°C, 40 bar and a H2 / CO ratio of about 3. These experiments were conducted at an isomerization conversion level with a CO conversion of about 65%. The volume of the balance gas was 10%.

[0068] Before contacting with the synthesis gas, the catalyst was heated to reaction temperature and pressure under nitrogen (N2). The reactor effluent composition was obtained by gas chromatography, and the conversion and carbon-based selectivity were calculated using the following equations:

[0069] WHSV (MMO+SAPO-34) =(F CO +F H2 ) / (W MMO +W SAPO-34 ) (1)

[0070] WHSV=(F CO +F H2 ) / W 催化剂 (2)

[0071] where F CO and F H2 are defined as the mass flow rates of CO and H2, respectively, and W MMO , W SAPO-34 and W 催化剂 are defined as the mass of the metal oxide catalyst component, the mass of the SAPO-34 component and the total catalyst mass (including binder), respectively.

[0072] X CO (%) = [(F CO, in -F CO, out ) / F CO, in ] · 100; and (3)

[0073] S j (%) = [α j · F j, out / (F CO, in -F CO, out )] · 100, (4)

[0074] Where X CODefined as CO conversion (%), F CO,in is defined as the molar inlet flow rate of CO (μmol / s), F CO,out is the molar outlet flow rate of CO (μmol / s), S j is defined as the carbonyl selectivity (%) for product j, α j is the number of carbon atoms in product j, F j,out is the molar outlet flow rate of product j (μmol / s). All data were collected under steady-state conditions after at least 40 hours of run time.

[0075] The results of the catalytic tests are described below. Examples 1 to 3 and Comparative Example 1 are reported in Figure 1 and Table 2. The measured CO conversions were normalized by the maximum CO conversion observed when the operating time (TOS) was close to zero, resulting in a normalized CO conversion as a function of TOS. The steady-state rate of CO conversion, C- 2- -C-4 olefin selectivity and methane selectivity, and the decay rate is obtained from the linearization between 50TOS and 350TOS. Specifically, FIG1 shows the normalized CO conversion of Examples 1 to 3 and Comparative Example 1 as a function of TOS. Figure 1A Comparative Example 1 curve 110 and Example 1 curve 112 are shown. Figure 1B Comparative Example 1 curve 114 and Example 2 curve 116 are shown. Figure 1C Example 1 curve 118 and Example 3 curve 120 are shown.

[0076] Table 2

[0077]

[0078] like Figure 1A As shown in Table 2, the addition of lanthanum to the metal oxide catalyst component caused the decay rate to increase from 2.57×10 -4 h -1 (Comparative Example 1) was reduced to 1.76×10 -4 h -1 (Example 1), while maintaining similar reaction rates and selectivities.

[0079] like Figure 1B As shown in Table 2, the increase in the calcination temperature of the metal oxide catalyst component from 550°C to 700°C resulted in a decrease in the decay rate from 2.57×10 -4 h -1 (Comparative Example 1) was reduced to 1.86×10 -4 h -1 (Example 2), while maintaining similar reaction rates and selectivities.

[0080] like Figure 1C As shown in Table 2, the increase in the calcination temperature of the metal oxide catalyst component containing lanthanum from 550°C to 700°C resulted in a decrease in the decay rate from 1.76×10 -4 h -1 (Example 1) is reduced to 1.0×10 -4 h -1 (Example 3), while maintaining similar reaction rates and selectivities.

[0081] As shown in Table 2, the increase in the calcination temperature of the metal oxide catalyst components and the incorporation of lanthanum resulted in a decrease in the decay rate from 2.57 × 10 -4 h -1 (Comparative Example 1) was reduced to 1.0×10 -4 h -1 (Example 3), while maintaining similar reaction rates and selectivities.

[0082] Comparison of Examples 1-3 and Comparative Example 1 shows the importance of the metal oxide catalyst component calcination temperature, the incorporation of lanthanum into the metal oxide catalyst component, or both, on the decay rate of the catalyst and therefore the stability of the catalyst during the conversion of synthesis gas to C2-C4 olefins.

[0083] The results of the catalytic tests of Example 4 and Comparative Example 2 are reported in Figure 2 and Table 3. As previously described, the normalized conversion of CO was measured as a function of time on stream (TOS). The steady-state rate of CO conversion, C- 2- -C-4 olefin selectivity and methane selectivity, and the decay rate is obtained from the linearization between 40TOS and 200TOS. Specifically, Figure 2 Normalized CO conversion as a function of TOS is shown for Example 4 and Comparative Example 2. Figure 2 Comparative Example 2 curve 210 and Example 4 curve 212 are shown.

[0084] Table 3

[0085]

[0086] like Figure 2 As shown in Table 3, the increase in the calcination temperature of the metal oxide catalyst component containing lanthanum in the hybrid catalyst from 550°C to 700°C resulted in a decrease in the decay rate from 2.58×10 -4 h -1 (Comparative Example 2) decreased to 2.13×10 -4 h -1(Example 4) while maintaining similar reaction rates and selectivities. This comparison shows the importance of the metal oxide catalyst component calcination temperature on the decay rate of the hybrid catalyst comprising the metal oxide catalyst component and therefore the stability of the catalyst during the conversion of synthesis gas to C2-C4 olefins.

[0087] Example 7

[0088] A metal oxide catalyst component comprising gallium and dysprosium on a zirconium oxide support was prepared by incipient wetness impregnation. An impregnation solution of gallium (III) nitrate hydrate (Ga(NO3)3·xH2O) and dysprosium (III) nitrate hydrate (Dy(NO3)3·xH2O) at concentrations of 0.86 mol / L and 0.86 mol / L, respectively, in deionized water was prepared. 2 g of a 60 mesh (250 μm) to 80 mesh (177 μm) ZrO2 support (manufactured by NORPRO, product code SZ31164, BET surface area = 100 m 2 / g, more than 95% monoclinic phase as measured by XRD, pore volume measured by deionized water = 0.4 mL / g) and placed in a glass vial. Afterwards, 0.8 mL of Ga and Dy impregnation solution was added dropwise to the support while shaking continuously. After impregnation, the metal oxide catalyst components were dried overnight at 80°C in a forced convection oven and calcined in a muffle furnace using the following procedure: heating from 25°C to 550°C at a heating rate of 3°C / min, and kept at 550°C for 4 hours. After calcination, the catalyst was re-screened to 60 to 80 mesh.

[0089] Example 8

[0090] A metal oxide catalyst component comprising gallium and samarium on a zirconium oxide support was prepared by incipient wetness impregnation. An impregnation solution of gallium (III) nitrate hydrate (Ga(NO3)3·xH2O) and samarium (III) nitrate hexahydrate (Sm(NO3)3·6H2O) at concentrations of 0.86 mol / L and 0.215 mol / L, respectively, in deionized water was prepared. 2 g of a 40 mesh (250 μm) to 80 mesh (177 μm) ZrO2 support (manufactured by NORPRO, product code SZ31164, BET surface area = 100 m 2 / g, more than 95% monoclinic phase by XRD, pore volume measured by deionized water = 0.4 mL / g) and placed in a glass vial. Afterwards, 0.8 mL of Ga and Sm impregnation solution was added dropwise to the support while shaking continuously. After impregnation, the metal oxide catalyst components were dried overnight at 80°C in a forced convection oven and calcined in a muffle furnace using the following procedure: heating from 25°C to 550°C at a heating rate of 3°C / min, and kept at 550°C for 4 hours. After calcination, the catalyst was re-screened to 60 to 80 mesh.

[0091] Example 9

[0092] A metal oxide catalyst component comprising gallium and gadolinium on a zirconium oxide support was prepared by incipient wetness impregnation. An impregnation solution of gallium (III) nitrate hydrate (Ga(NO3)3·xH2O) and gadolinium (III) nitrate hexahydrate (Gd(NO3)3·6H2O) at concentrations of 0.86 mol / L and 0.86 mol / L, respectively, in deionized water was prepared. 2 g of a 40 mesh (250 μm) to 80 mesh (177 μm) ZrO2 support (manufactured by NORPRO, product code SZ31164, BET surface area = 100 m 2 / g, more than 95% monoclinic phase by XRD, pore volume measured by deionized water = 0.4 mL / g) and placed in a glass vial. Afterwards, 0.8 mL of Ga and Gd impregnation solution was added dropwise to the support while shaking continuously. After impregnation, the metal oxide catalyst components were dried overnight at 80°C in a forced convection oven and calcined in a muffle furnace using the following procedure: heating from 25°C to 550°C at a heating rate of 3°C / min, and kept at 550°C for 4 hours. After calcination, the catalyst was re-screened to 60 to 80 mesh.

[0093] Comparative Example 3

[0094] A metal oxide catalyst component containing gallium on a zirconium oxide support was prepared by incipient wetness impregnation. An impregnation solution of gallium (III) nitrate hydrate (Ga(NO3)3·xH2O) at a concentration of 0.86 mol / L in deionized water was prepared. 2 g of a 60 mesh (250 μm) to 80 mesh (177 μm) ZrO2 support (manufactured by NORPRO, product code SZ31164, BET surface area = 100 m 2 / g, more than 95% monoclinic phase obtained by XRD, pore volume measured by deionized water = 0.4 mL / g) and placed in a glass vial. After that, 0.8 mL of Ga impregnation solution was added dropwise to the support while shaking continuously. After impregnation, the metal oxide catalyst component was dried overnight at 80°C in a forced convection oven and calcined in a muffle furnace using the following procedure: heating from 25°C to 550°C at a heating rate of 3°C / min, and kept at 550°C for 4 hours. After calcination, the catalyst was re-screened to 60 mesh to 80 mesh.

[0095] Example 10 - Catalytic Performance Data

[0096] Prior to testing, the mixed metal oxide catalysts described in Examples 7 to 9 and Comparative Example 3 were physically mixed with calcined SAPO-34 of 60-80 mesh sieve fraction at a mass ratio of 1:1. Testing of the hybrid catalysts was carried out in a quartz fixed bed reactor system (4 mm inner diameter) under the following conditions: 460°C, 40 bar, 3 h -1 The reaction mixture was stirred at a weight hourly space velocity (WHSV) of about 1.0 and a H2 / CO ratio of about 3.

[0097] Before contacting with synthesis gas, the catalyst was heated to reaction temperature and pressure under nitrogen (N2). The reactor effluent composition was obtained by gas chromatography, and conversion and carbon-based selectivity were calculated using equations (1) to (4). All data were collected under steady-state conditions after at least 40 hours of run time.

[0098] Table 4

[0099]

[0100] As shown in Table 4, the addition of rare earth elements to the metal oxide catalyst component caused the decay rate to increase from 2.61×10 -4 h -1 (Comparative Example 3) decreased to 0.64×10 -4 -1.59×10 -4 (Example 7 to Example 9), while maintaining similar reaction rates and selectivities.

[0101] It should be noted that one or more of the following claims utilize the term "where" or "in which" as a transitional phrase. For purposes of defining the present technology, it should be noted that this term is introduced in the claims as an open transitional phrase that is used to introduce a recitation of a series of characteristics of a structure and should be interpreted in a manner similar to the more commonly used open preamble term "comprising". For purposes of defining the present technology, the transitional phrase "consisting of" may be introduced in a claim as a closed preamble term that limits the scope of the claim to the listed components or steps and any naturally occurring impurities. For purposes of defining the present technology, the transitional phrase "consisting essentially of" may be introduced in a claim to limit the scope of one or more claim items to the stated elements, components, materials, or method steps and any non-stated elements, components, materials, or method steps that do not materially affect the novel characteristics of the claimed subject matter. The transition phrases "consisting of" and "consisting essentially of" may be interpreted as a subset of open transition phrases, such as "comprising" and "including", such that any use of an open phrase to introduce a statement of a list of elements, components, materials, or steps should be interpreted as also disclosing the statement of the list of elements, components, materials, or steps using the closed terms "consisting of" and "consisting essentially of". For example, a statement that a composition "comprising" components A, B, and C should be interpreted as also disclosing a composition "consisting of" components A, B, and C as well as a composition "consisting essentially of" components A, B, and C. Any quantitative value expressed in this application may be considered to include open embodiments that conform to the transition phrases "comprising" or "comprising" as well as closed or partially closed embodiments that conform to the transition phrases "consisting of" and "consisting essentially of".

[0102] As used in the specification and the appended claims, the singular forms "a", "an", and "the" include plural references unless the context clearly indicates otherwise. The verb "comprise" and its cognate forms should be interpreted as referring to elements, components, or steps in a non-exclusive manner. The referenced elements, components, or steps may exist, be utilized, or be combined with other elements, components, or steps that are not explicitly referenced.

[0103] It should be understood that any two quantitative values ​​assigned to a characteristic may constitute a range for that characteristic, and all combinations of ranges formed by all said quantitative values ​​of a given characteristic are considered in the present disclosure. The subject matter of the present disclosure has been described in detail and by reference to specific embodiments. It should be understood that any detailed description of a component or feature of one or more embodiments does not necessarily imply that the component or feature is necessary for a particular embodiment or any other embodiment. Further, it will be apparent to those skilled in the art that various modifications and changes may be made to the described embodiments without departing from the essence and scope of the claimed subject matter.

Claims

1. A method for preparing C2 to C4 hydrocarbons, the method comprising: introducing a feed stream comprising hydrogen and a carbon-containing gas selected from the group consisting of carbon monoxide, carbon dioxide, and mixtures thereof into a reaction zone of a reactor; as well as The feed stream is converted into a product stream comprising C2 to C4 hydrocarbons in the reaction zone in the presence of a hybrid catalyst, wherein The hybrid catalyst comprises: a metal oxide catalyst component supported on zirconium oxide, the metal oxide catalyst component comprising gallium oxide and a rare earth oxide; and A microporous catalyst component comprising a molecular sieve having 8-MR (membered ring) pore openings.

2. The method of claim 1, wherein the metal oxide catalyst component comprises greater than 1 wt% and less than or equal to 7 wt% of one or more rare earth elements.

3. A process according to any preceding claim, wherein the metal oxide catalyst component comprises less than or equal to 10 wt% gallium.

4. A process according to any preceding claim, wherein the metal oxide catalyst component comprises from 40.0 wt% to 90.0 wt% of the hybrid catalyst.

5. A process according to any preceding claim, wherein the metal oxide catalyst component further comprises nickel, palladium or platinum.

6. The method of any preceding claim, wherein the rare earth oxide comprises samarium, gadolinium, dysprosium, lanthanum, cerium, neodymium, yttrium or a combination of two or more thereof.

7. A method according to any preceding claim, wherein the microporous catalyst component comprises SAPO-34.

8. A process according to any preceding claim, wherein the metal oxide catalyst component comprises less than 0.5 wt% silicon and phosphorus.

9. A process according to any preceding claim, wherein during the conversion the temperature in the reaction zone is from 350°C to 480°C.

10. A process according to any preceding claim, wherein the C2-C4 hydrocarbons comprise 50 wt% or greater C2-C4 olefins.

11. A method according to any preceding claim, wherein the metal oxide catalyst component is calcined at a temperature of 400°C to 800°C to form a calcined metal oxide catalyst component prior to mixing with the microporous catalyst component.

12. The method of claim 11, wherein the metal oxide catalyst component is calcined at a temperature of 550°C to 700°C.

13. The method of any one of claims 11 or 12, wherein the calcined metal oxide catalyst component is physically mixed with the microporous catalyst component.

14. The method according to any one of claims 11 or 12, wherein mixing the calcined metal oxide catalyst component and the microporous catalyst component with a binder to form a paste, extruding the paste to produce a hybrid catalyst, drying and calcining the hybrid catalyst, and The binder is a colloidal solution, suspension or gel of a binder precursor comprising an oxide or hydroxide of aluminum, an oxide or hydroxide of zirconium or a mixture thereof.

15. The method of claim 14, wherein the binder comprises less than 0.5 wt% silicon and phosphorus.